School Climate: A Comparative Study from the Perspective of Kindergarten Principals and Teachers - Abdulhamit Karademir; Meral Ören (Anı Publishing, 2020)
The aim of this study is to determine the school climate in formal kindergartens, to examine the factors affecting it and its effect on education and to use teachers and school principals' views to point out the elements necessary for its improvement. Partially mixed sequential dominant status design, which is a two-stage (qualitative and qualitative) mixed design was used in the study. In the first stage, 115 teachers and 34 school principals of 18 independent kindergartens in Eskişehir were administered an Organizational Climate Scale to determine the working climates of the kindergartens. In the second stage, semi-structured interviews were conducted with the teachers and principals of the two schools with the highest and lowest scale scores to investigate the reasons for the differences in school climates and their effect on education. Principals' personalities and their communication and problem solving skills, and support, praise and encouragement given to teachers, fair behavior, openness to new ideas and involving staff in decision making play an important role in creating a positive school climate. School climate has a great impact on students through teachers and staff.